Analisis perspektif kritis generasi z terhadap wacana pada media sosial - Kasmantoni Kasmantoni; Pebri Prandika Putra (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to know the perspective of Gen Z in understanding the discourse contained in social media. The perspective means the ability to change Gen z’s perspective in understanding the text on social media, the ability to see points of view, focus on a developing issue, and describe how to take action after understanding a discourse. The research method used the quantitative method. Respondents of this research are Gen Z, who are active in youth organizations. Data collection techniques are observation and questionnaire. The results showed that Gen Z had detected a discourse that contains partiality to certain interests by providing a different perspective. It can be seen in the positive response on the average instrument (mean) above 53%; able to provide a more neutral point of view with the number of positive responses on the average instrument above (mean) 51%; able to see a developing issue in a discourse that has a tendency from the author with a positive response above 56%; and able to take action from the discourse that has been read with an average positive response above 59%.